Deteksi Manajemen Laba Melalui Karakteristik Perusahaan: Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Lulu Nailufaroh; Dian Maulita; Dien Sefty Framita (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2024)
Earnings management is a way for company managers to change the information contained in financial reports with the aim of deceiving stakeholders who want to know the performance and condition of the company (Sulistyanto, 2014). The aim of this research is to test and analyze variables that can influence earnings management in chemical industry companies in 2019-2021. Researchers use independent variables, namely company characteristics. Company characteristics are measured by company size and financial leverage. The collected research data was processed through various regression analysis techniques and sampling techniques using purposive sampling. The research results show that leverage has no effect on earnings management, while company size has a significant negative effect on earnings management.